Ramadan Mubarak - Khan, Saniyasnain (Ajman, U.A.E Iqra Book distribution, 2024)
* The doors of the Paradise are open in Ramadan * We fast, pray and read the Quran during Ramadan * The fasting person learns patience and self-discipline * We develop a sense of compassion and sympathy * We try to do good deeds and maintain good habits * In the end, we celebrate Eid ul Fitr with a big feast